LINGKUNGAN BELAJAR DI SEKOLAH DENGAN HASIL BELAJAR IPS DI SMP - Fitriyah, Fitriyah; Mashudi, Mashudi; Buwono, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aimed to find out how much influence the learning environment in school had on studentsâ€™ learning outcome in Social Sciences at seven grades in SMP Negeri 20 Pontianak. The method that used is descriptive with the form correlation. Population and sample in this study were grade seven of students and the data collected by using a questionnaire. It was about learning environment at the school. Learning environment also influences the students learning outcomes because learning environment was the second environment which had students after the family.From the results in this research that conducted at SMP Negeri 20 Pontianak. Learning environment can be classified as the data described in chapter IV, therefore the correlation of variables (X) and variables (Y) based on the technique of data collection and data analysis. It relates between learning environment at school with learning outcomes of 0.660. With a standard that had been set at 0.05 at a significant level and n-2 = 65-2 = 63 that is 0.2441. So that showed that the result was equal to r count> r table 0,660> 0,2441. So that the relations of the learning environment in schools with learning outcomes of 0.660 is classified as strong.Â Keywords: Learning Environment in Schools, Student Learning Outcomes